Understanding Gen Z’s Debt Behavior: Interplay of Knowledge, Self-Efficacy, and Psychological Stress - Putri Renalita Sutra Tanjung; Wieta Chairunesia; Tine Yuliantini; Anees Janee Ali; Primanita Oktasari, Dian (Jurnal Internasional Penelitian Bisnis Terapan, 2026)
This research aims to analyze the impact of Financial Knowledge, Financial Self-Efficacy, and Financial Stress on debt usage behavior among Generation Z, employing the framework of the Theory of Planned Behavior (TPB). A quantitative methodology utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM) was adopted for this study. Data were collected through an online survey involving 100 Generation Z respondents in Indonesia. The findings indicate that Financial Knowledge positively influences both Financial Self-Efficacy and Financial Stress. Furthermore, Financial Self-Efficacy is associated with a reduction in the tendency to incur debt, whereas Financial Stress tends to increase it. Both variables serve as mediators between Financial Knowledge and debt usage behavior. These findings underscore the significance of financial literacy, coupled with enhanced self-confidence in financial management and effective financial stress management, to mitigate the risks of excessive debt among Generation Z. This study contributes to the development of the TPB model by incorporating psychological and emotional dimensions in the financial decision-making processes of young individuals.